Focus stacking photogrammetry for micro‐scale roughness reconstruction: a methodological study. (25th March 2019) - Olkowicz, Marcin; Dabrowski, Marcin; Pluymakers, Anne
Abstract: In close‐range applications, it is unclear whether optical photogrammetry is capable of accurately reconstructing submillimetre‐scale roughness. This paper presents a study of fine‐scale rock fracture roughness measurements with a careful assessment of the error. The workflow combines the techniques of structure from motion with focus stacking, using consumer‐grade equipment and free or affordable software. The approach is tested firstly with synthetic data to check the influence of the number and position of cameras, object texture and image processing using focus stacking. Secondly, the optimised workflow is used to measure a natural shale rock fracture surface. To estimate the accuracy, the results were compared with a high‐precision reference dataset provided by white‐light interferometry. The standard deviation of error in the method is 6·5 μm, and is related with morphological structures with wavelengths below 150 μm and amplitudes smaller than 10 μm. Abstract : This paper presents a study of submillimetre‐scale rock fracture roughness measurements using optical close range photogrammetry with a careful assessment of the error. The workflow combines structure from motion with focus stacking, using consumer‐grade equipment and free or affordable software. The approach is tested with both synthetic data and a natural shale rock fracture surface. To estimate the accuracy, the results were compared with a high‐precision reference dataset provided by white light interferometry.